Reconfiguration of distribution system and optimal dg placement DG to enhance voltage profile and reduce losses - Ravi Kumar, Thummala; Kesava Rao, Gattu (International Journal of Engineering and Technology, 2018)
System reconfiguration which is compelled non linear enhancement issue has been tackled for loss minimization, load balancing, and so on. Another factor of equivalent significance is of DG plays a critical responsibility in the management of distribution system. Itâ€™s important to optimize its size and location in order extract maximum benefits of its placement. There are number reasons for optimizing the location and sizing, chief among them being reduce power loss and enhancement of voltage profile. Here a hybrid algorithm is proposed for reconfiguration and DG siting is employed to enhance the benefits of DG placement. Non Sorted Genetic Algorithm (NSGA) is employed to reconfigure the distribution system prior to the placement of DG. Once the system is reconfigured, Particle Swarm Optimization (PSO) is employed to recognize the ideal size and placement of DG. The results exhibit the suitability of this combined algorithm in terms reduced power losses and enhanced voltage profile. Results are compared and analyzed for DG placement with and without reconfiguration for IEEE 69 bus distribution system.Â Â